Anmeldelse - Bak, Kirsten Sass (Modspil, 1989)
Anmeldelse af Vagn Holmboe: Danish Street Cries. A study of their musical structure and a complete edition of tunes with words collected before 1960. Forlaget Kragen ApS 1988.